Analysis Study Of Modernization And Problems In Islamic Education - Rian Anugrah Firmanto; Kasful Anwar US; As'ad Isma (Cita konsultindo, 2023)
The modernization of islamic Education continues to be pursued, but these efforts are still faced with endless problems, so an effort is needed, including starting with an effective and efficient approach, goals and steps to advance Islamic Education so that it can compete in the world. the current era of globalization. the concept of modernizing Islamic education includes thoughts about modernizing goals, curricula and institutions of Islamic Education. The goal of Islamic education today is to have a balance, namely happiness in the world and the hereafter, as well as increasing capabilities in the field of science and technology. The Islamic Education Curriculum needs to be included in the field of science and technology so that superior human resources will be created not only in the field of religion but also in science and technology. Islamic Education Institutions also need to be managed in a professional and directed manner in order to achieve satisfactory results in developing the potential of students. The concept of modernization of education is still relevant to the concept of Islamic Education contained in the Al-Qur'an and Hadith. It can be seen from the similarity in the formulation of the goals of Islamic Education, namely that they both pay attention to two things, namely the happiness of the world and also the hereafter at the same time. Besides that, it is also related to the characteristics of Islamic education, the concept of Islamic Education contained in the Qur'an equally pays attention to the mastery of science and technology. Problems that are a challenge for Islamic educational institutions in improving quality include: public skepticism towards Islamic educational institutions, weak institutional vision and mission, overloaded curricula, low competitiveness of graduates of educational institutions and inadequate infrastructure.